Clarifying associations between childhood adversity, social support, behavioral factors, and mental health, health, and well-being in adulthood: A population-based study - Mashhood Ahmed Sheikh; Birgit eAbelsen; Jan Abel Olsen (Frontiers in Psychology, 2016)
Previous studies have shown that socio-demographic factors, childhood socioeconomic status (CSES), childhood traumatic experiences (CTEs), social support and behavioural factors are associated with health and well-being in adulthood. However, the relative importance of these factors for mental health, health, and well-being has not been studied. Moreover, the mechanisms by which CTEs affect mental health, health, and well-being in adulthood are not clear. Using data from a representative sample (n=12,981) of the adult population in Tromsø, Norway, this study examines (i) the relative contribution of structural conditions (gender, age, CSES, psychological abuse, physical abuse, and substance abuse distress) to social support and behavioural factors in adulthood ; (ii) the relative contribution of socio-demographic factors, CSES, CTEs, social support, and behavioural factors to three multi-item instruments of mental health (SCL-10), health (EQ-5D), and subjective well-being (SWLS) in adulthood; (iii) the impact of CTEs on mental health, health, and well-being in adulthood, and; (iv) the mediating role of adult social support and behavioural factors in these associations. Instrumental support (24.16%, p<0.001) explained most of the variation in mental health, while gender (21.32%, p<0.001) explained most of the variation in health, and emotional support (23.34%, p<0.001) explained most of the variation in well-being. Psychological abuse was relatively more important for mental health (12.13%), health (7.01%), and well-being (9.09%), as compared to physical abuse, and substance abuse distress. The subjective assessment of childhood financial conditions was relatively more important for mental health (6.02%), health (10.60%), and well-being (20.60%), as compared to mother’s and father’s education. CTEs were relatively more important for mental health, while, CSES was relatively more important for health and well-being. Respondents exposed to all three types of CTEs had a more than two-fold risk of being mentally unhealthy (RR=2.75, 95% CI: 2.19-3.10), an 89% increased risk of being unhealthy (RR=1.89, 95% CI: 1.47-1.99), and a 42% increased risk of having a low level of well-being in adulthood (RR=1.42, 95% CI: 1.29-1.52). Social support and behavioural factors mediate 11-18% (p<0.01) of these effects. The study advances the theoretical understanding of how CTEs influence adult mental health, health, and well-being.